JURIDICAL ANALYSIS OF LAW ENFORCEMENT AGAINST FOREIGN SHIP WITHOUT A LICENSE TO OPERATE IN THE RIAU ISLANDS TO REALIZE LEGAL GUARANTEE IN SOVEREIGNTYNATIONS (RESEARCH STUDY OF MARINE SERVICE LOCATIONS AND CLASS II BEACH, TANJUNG UBAN) - Amir, Muhammad; Wasliwati, Laily; Parroha Patar Siadari, Lagat (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
What factors are the obstacles and solutions in law enforcement efforts against foreign ships without a permit to operate in the Riau Islands region to realize legal certainty in the sovereignty of the nation? The type of research is normative legal writing, using legal research methodology, supported by secondary data and literature. For the grand theory, using the theory of Justice (Justice Theory) as a grand theory is a theory building structure that has abstraction power. Middle Theory uses the theory of legal certainty by Mochtar Kusumaatmadja, Applied Theory uses the theory of legal system law from Lawrence M. Friedman. The results of the analysis concluded that the KPLP was formed to ensure the implementation of safety and security at sea and to enforce laws and regulations at sea and coast.